Composite lithium supplement agent and preparation method and application thereof

The vanadium source layer and graphene and cellulose composite layer on the surface of the lithium supplement agent are coated through double coating technology, which solves the problems of existing lithium supplement agents being sensitive to air, difficult to process and storage, and achieves higher tolerance and conductivity, and extends the cycle life of lithium-ion batteries.

CN119921006AActive Publication Date: 2025-05-02XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510089331.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-05-02
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The existing lithium supplement products have high residual alkali content, are sensitive to air, are difficult to process, are difficult to store, and are inactive after one discharge, affecting the performance of the battery cell.

Method used

The composite lithium supplement agent is used to coat the vanadium source layer and the graphene and cellulose composite layer on the surface of the lithium supplement agent through double coating technology to isolate the moisture and CO2 in the external air, reduce the residual alkali content, and form a conductive polymer to improve the conductivity and material dispersion.

Benefits of technology

It improves the tolerance of lithium supplements to the storage environment, improves the feasibility of application in battery cell manufacturing and processing, extends the cycle life of lithium-ion batteries, and reduces polarization and internal resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005251039230000121
    Figure BDA0005251039230000121
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a composite lithium supplement agent and a preparation method and application thereof. The composite lithium supplement agent comprises a lithium supplement agent, the surface of the lithium supplement agent is coated with the vanadium source layer; the surface of the vanadium source layer is coated with the graphene and cellulose composite layer. The composite lithium supplement agent has the beneficial effects that the residual alkali content is reduced, the gas production rate is low, the conductivity is relatively high, the charge-discharge performance of a battery can be improved, and the cycle service life of the battery can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and specifically relates to a composite lithium supplement agent and a preparation method and application thereof. Background Art

[0002] In the current commercial lithium-ion battery manufacturing process, after the battery cell is assembled, shelled, baked, and injected, during the first charge and discharge process, the lithium ions and the electrolyte undergo an irreversible reaction at the solid-liquid interface between the electrode and the electrolyte to form a layer of solid electrolyte membrane, namely the SEI membrane. This process causes irreversible consumption of lithium ions. During the subsequent cyclic charge and discharge of the battery cell, various aging conditions cause irreversible consumption of lithium ions, resulting in degradation of the battery cell performance and reduced service life. In the prior art, the irreversibly consumed lithium ions are compensated by adding a lithium supplement to the positive electrode. The lithium supplement can release lithium ions during the first charge and discharge or continue to release lithium ions in subsequent cyclic charge and discharge, thereby increasing the cycle life of the battery cell.

[0003] However, existing lithium supplement products have high residual alkali content and are sensitive to air. They are difficult to process and preserve in battery cell applications. In addition, some lithium supplements lose their activity after a single discharge and remain in the battery cell electrodes, affecting performance. Summary of the invention

[0004] The present application provides a composite lithium supplement agent and a preparation method and application thereof, aiming to solve the problems that the lithium supplement agent is sensitive to air, difficult to process, and difficult to preserve, improve its performance, and increase the cycle life of lithium-ion batteries.

[0005] In a first aspect, the present application provides a composite lithium supplement, comprising a lithium supplement; a vanadium source layer coated on the surface of the lithium supplement; and a graphene and cellulose composite layer coated on the surface of the vanadium source layer.

[0006] After double coating, the composite lithium supplement agent described in the present application largely isolates moisture and CO2 in the external air from reacting with the core of the lithium supplement agent, thereby improving the tolerance of the lithium supplement agent to the storage environment and improving the feasibility of the effective application of the lithium supplement agent in battery cell manufacturing and processing.

[0007] In addition, the residual alkali content on the surface of the double-coated lithium supplement is reduced, which can reduce the reaction activity between it and the electrolyte and reduce gas production. The metal compound in the lithium supplement has a good spatial structure with the vanadium oxide or vanadate, which can form a channel for the rapid diffusion of ions or electrons. After the cellulose composite powder is mixed and coated in the ethanol solution, it can not only fill the gaps between the metal compounds to form a dense protective layer, but also produce conductive polymers after low-temperature sintering, which can enhance the overall conductivity of the lithium supplement, reduce polarization, and improve the charge and discharge performance of the battery. At the same time, it reduces particle agglomeration during the homogenization process and improves the dispersion of the material.

[0008] According to some embodiments of the composite lithium supplement described in the present application, the lithium supplement includes a lithium source and a metal compound.

[0009] According to some embodiments of the composite lithium supplement described in the present application, the lithium source includes one or more of LiOH, Li2CO3, Li2O, Li2O2, LiNO3 and Li2SO4.

[0010] According to some embodiments of the composite lithium supplement described in the present application, the metal compound includes one or more of Fe2O3, Fe3O4, FeCl3, Fe(OH)3, NiO, NiSO4 and Ni(OH)2.

[0011] According to some embodiments of the composite lithium supplement described in the present application, the molar ratio of the lithium source to the metal compound is (2-7):1.

[0012] According to some embodiments of the composite lithium supplement agent described in the present application, the particle size D50 of the lithium supplement agent is 8-13 um.

[0013] According to some embodiments of the composite lithium supplement described in the present application, the vanadium source layer includes vanadyl oxalate, ammonium metavanadate, vanadium pentoxide, V6O 13 , VO2(B) and V2O3.

[0014] According to some embodiments of the composite lithium supplement agent described in the present application, the mass ratio of the lithium supplement agent to the vanadium source layer is 100:(1-8), preferably 100:(3-5).

[0015] According to some embodiments of the composite lithium supplement described in the present application, the cellulose includes one or more of hydroxypropyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, hydroxyethyl cellulose and ethyl cellulose.

[0016] According to some embodiments of the composite lithium supplement described in the present application, the cellulose includes one or more of hydroxypropyl cellulose, hydroxypropyl methyl cellulose and ethyl cellulose.

[0017] According to some embodiments of the composite lithium supplement described in the present application, the mass ratio of the graphene to the cellulose is 1:(0.6-1.6), preferably 1:(0.8-1.3).

[0018] According to some embodiments of the composite lithium supplement agent described in the present application, the mass ratio of the total mass of the lithium supplement agent and the vanadium source layer to the mass of the composite layer is 100:(1-8).

[0019] According to some embodiments of the composite lithium supplement agent described in the present application, the particle size D50 of the composite lithium supplement agent is 8-13 um.

[0020] The second aspect of the present application provides a method for preparing the composite lithium supplement agent described in the first aspect of the present application, comprising the following steps:

[0021] (1) mixing a lithium supplement agent and a vanadium source and performing a first sintering to obtain a lithium supplement agent intermediate coated with a vanadium source layer;

[0022] (2) mixing the lithium supplement intermediate, graphene, cellulose and an organic solvent to obtain a mixed solution;

[0023] (3) filtering the mixed solution, drying the solid matter obtained by filtration and performing a second sintering to obtain the composite lithium supplement agent.

[0024] The preparation method described in the present application preferentially coats the vanadium source to form a non-inert coating layer, which can provide an ion channel for the lithium supplement and improve the ion conductivity. The pre-mixed graphene and cellulose materials are then coated for a second time to fill the defects formed by the first coating layer, provide secondary protection, and form a dense electronic conductive network to improve the conductivity of the powder.

[0025] According to some embodiments of the method for preparing the composite lithium supplement agent described in the present application, in step (1), the method for preparing the lithium supplement agent includes the following steps: mixing a lithium source and a metal compound and ball milling them, and sintering the ball milling product in a vacuum environment to obtain the lithium supplement agent.

[0026] According to some embodiments of the method for preparing the composite lithium supplement agent described in the present application, the rotation speed of the ball mill is 600-1200 r / min, and the time of the ball mill is 2-5 h.

[0027] According to some embodiments of the method for preparing the composite lithium supplement agent of the present application, the temperature of the sintered ball milled product is 700-1000° C., and the time of sintering the ball milled product is 2-6 hours;

[0028] According to some embodiments of the method for preparing the composite lithium supplement described in the present application, the heating rate of the sintered ball-milled product is 5-15° C. / min.

[0029] According to some embodiments of the method for preparing the composite lithium supplement described in the present application, the first sintering is performed in an inert atmosphere. Preferably, the inert atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.

[0030] According to some embodiments of the method for preparing the composite lithium supplement described in the present application, the temperature of the first sintering is 200-500° C., and the time of the first sintering is 2-6 hours.

[0031] According to some embodiments of the method for preparing the composite lithium supplement described in the present application, the heating rate of the first sintering is 5-15° C. / min.

[0032] According to some embodiments of the method for preparing the composite lithium supplement agent described in the present application, the particle size D50 of the lithium supplement agent intermediate is 8-13 um.

[0033] According to some embodiments of the method for preparing a composite lithium supplement agent described in the present application, in step (2), the graphene, the cellulose and the organic solvent are first mixed, and the first mixed product is filtered and dried to obtain a cellulose composite powder; and then the cellulose composite powder, the lithium supplement agent intermediate and the organic solvent are second mixed.

[0034] According to some embodiments of the method for preparing the composite lithium supplement described in the present application, the speed of the first mixing is 1000-1600 r / min, and the time of the first mixing is 2-5 h.

[0035] According to some embodiments of the method for preparing the composite lithium supplement described in the present application, in the first mixing step, the solid-to-liquid ratio of the graphene and the cellulose to the organic solvent is (0.1-0.2) mg:1 ml.

[0036] According to some embodiments of the method for preparing the composite lithium supplement described in the present application, the organic solvent includes ethanol and / or N-methylpyrrolidone.

[0037] According to some embodiments of the method for preparing a composite lithium supplement described in the present application, the particle size D50 of the cellulose composite powder is ≤30 um.

[0038] According to some embodiments of the method for preparing the composite lithium supplement agent described in the present application, in the second mixing step, the solid-liquid ratio of the lithium supplement agent intermediate and the cellulose composite powder to the organic solvent is (1-10) mg: 1 ml.

[0039] According to some embodiments of the method for preparing the composite lithium supplement described in the present application, the speed of the second mixing is 1000-1600 r / min, and the time of the second mixing is 0.5-2 h.

[0040] According to some embodiments of the method for preparing a composite lithium supplement described in the present application, in step (3), the second sintering is performed under an inert atmosphere. Preferably, the inert atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.

[0041] According to some embodiments of the method for preparing the composite lithium supplement described in the present application, in step (3), the temperature of the second sintering is 200-400° C., and the time of the second sintering is 1-3 hours.

[0042] According to some embodiments of the method for preparing the composite lithium supplement described in the present application, in step (3), the heating rate of the second sintering is 2-10° C. / min.

[0043] The third aspect of the present application provides a lithium ion battery, wherein the positive electrode of the lithium ion battery comprises the composite lithium supplement agent described in the first aspect of the present application or the composite lithium supplement agent obtained by the preparation method described in the second aspect of the present application.

[0044] According to some embodiments of the lithium-ion battery described in the present application, the mass percentage of the composite lithium supplement in the positive electrode material of the lithium-ion battery is 0.1%-10%. DETAILED DESCRIPTION

[0045] Embodiments of the present invention are described in detail below. The examples of the embodiments are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0046] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0047] The embodiment of the present application provides a composite lithium supplement, including a lithium supplement;

[0048] A vanadium source layer coated on the surface of the lithium supplementing agent;

[0049] A graphene and cellulose composite layer coated on the surface of the vanadium source layer.

[0050] After double coating, the composite lithium supplement agent described in the present application largely isolates moisture and CO2 in the external air from reacting with the core of the lithium supplement agent, thereby improving the tolerance of the lithium supplement agent to the storage environment and improving the feasibility of the effective application of the lithium supplement agent in battery cell manufacturing and processing.

[0051] In addition, the residual alkali content on the surface of the double-coated lithium supplement is reduced, which can reduce the reaction activity between it and the electrolyte and reduce gas production. The metal compound in the lithium supplement has a good spatial structure with the vanadium oxide or vanadate, which can form a channel for the rapid diffusion of ions or electrons. After the cellulose composite powder is mixed and coated in the ethanol solution, it can not only fill the gaps between the metal compounds to form a dense protective layer, but also produce conductive polymers after low-temperature sintering, which can enhance the overall conductivity of the lithium supplement, reduce polarization, and improve the charge and discharge performance of the battery. At the same time, it reduces particle agglomeration during the homogenization process and improves the dispersion of the material.

[0052] In some embodiments of the present application, the lithium supplement comprises a lithium source and a metal compound.

[0053] In some embodiments of the present application, the lithium source includes one or more of LiOH, Li2CO3, Li2O, Li2O2, LiNO3 and Li2SO4.

[0054] In some embodiments of the present application, the metal compound includes one or more of Fe2O3, Fe3O4, FeCl3, Fe(OH)3, NiO, NiSO4 and Ni(OH)2.

[0055] In some embodiments of the present application, the molar ratio of the lithium source to the metal compound is (2-7):1, for example, 2:1, 3:1, 4:1, 5:1, 7:1, etc.

[0056] In some embodiments of the present application, the particle size D50 of the lithium supplement is 8-13um, for example, 8um, 9um, 9.5um, 10.2um, 10.8um, 11.3um, 11.8um, 12.6um, 13um, etc.

[0057] In some embodiments of the present application, the vanadium source layer includes vanadyl oxalate, ammonium metavanadate, vanadium pentoxide, V6O 13 , VO2(B) and V2O3.

[0058] Vanadium salts or vanadium oxides can be coated on the surface of the lithium supplement to inhibit further reaction between the lithium supplement and moisture in the air, and their interlayer structure can greatly promote the Li + The free diffusion of ions improves their ionic conductivity.

[0059] In some embodiments of the present application, the mass ratio of the lithium supplement and the vanadium source layer is 100:(1-8), for example, 100:1, 100:2.5, 100:3, 100:3.6, 100:4.3, 100:4.8, 100:5.2, 100:6.3, 100:7.1, 100:8, etc.

[0060] In some embodiments of the present application, the mass ratio of the lithium supplement agent to the vanadium source layer is 100:(3-5).

[0061] In some embodiments of the present application, the cellulose includes one or more of hydroxypropyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, hydroxyethyl cellulose and ethyl cellulose.

[0062] In some embodiments of the present application, the cellulose includes one or more of hydroxypropyl cellulose, hydroxypropyl methyl cellulose and ethyl cellulose.

[0063] The celluloses described in the present application are all cellulose ether derivatives, which are stable in nature, widely available, easy to use, and easily soluble in organic solvents. Hydroxypropyl cellulose, hydroxypropyl methyl cellulose, and ethyl cellulose are further preferred.

[0064] In some embodiments of the present application, the mass ratio of the graphene to the cellulose is 1:(0.6-1.6), for example, 1:0.6, 1:0.8, 1:1.2, 1:1.4, 1:1.6, etc.

[0065] In some embodiments of the present application, the mass ratio of the graphene to the cellulose is 1:(0.8-1.3).

[0066] In some embodiments of the present application, the mass ratio of the total mass of the lithium supplement and the vanadium source layer to the composite layer is 100:(1-8), for example, 100:1, 100:2, 100:2.6, 100:3.2, 100:4.6, 100:5.3, 100:6, etc.

[0067] In some embodiments of the present application, the particle size D50 of the composite lithium supplement is 8-13um, for example, 8um, 9um, 10um, 11um, 12um, 13um, etc.

[0068] The present application also provides a method for preparing the composite lithium supplement agent according to the first aspect of the present application, comprising the following steps:

[0069] (1) mixing a lithium supplement agent and a vanadium source and performing a first sintering to obtain a lithium supplement agent intermediate coated with a vanadium source layer;

[0070] (2) mixing the lithium supplement intermediate, graphene, cellulose and an organic solvent to obtain a mixed solution;

[0071] (3) filtering the mixed solution, drying the solid matter obtained by filtration and performing a second sintering to obtain the composite lithium supplement agent.

[0072] The preparation method described in the present application preferentially coats the vanadium source to form a non-inert coating layer, which can provide an ion channel for the lithium supplement and improve the ion conductivity. The pre-mixed graphene and cellulose materials are then coated for a second time to fill the defects formed by the first coating layer, provide secondary protection, and form a dense electronic conductive network to improve the conductivity of the powder.

[0073] In some embodiments of the present application, in step (1), the method for preparing the lithium supplement comprises the following steps: mixing a lithium source and a metal compound and ball milling them, and sintering the ball milling product in a vacuum environment to obtain the lithium supplement.

[0074] In some embodiments of the present application, the ball milling rotation speed is 600-1200r / min, for example, 600r / min, 680r / min, 720r / min, 780r / min, 830r / min, 890r / min, 930r / min, 1100r / min, 1200r / min, etc., and the ball milling time is 2-5h, for example, 2h, 3h, 4h, 5h, etc.

[0075] In some embodiments of the present application, the temperature of the sintered ball-milled product is 700-1000°C, for example, 700°C, 780°C, 830°C, 880°C, 960°C, 1000°C, etc., and the sintering time of the ball-milled product is 2-6h, for example, 2h, 3h, 4h, 6h, etc.

[0076] In some embodiments of the present application, the heating rate of the sintered ball-milled product is 5-15°C / min, for example, 5°C / min, 8°C / min, 10°C / min, 12°C / min, 15°C / min, etc.

[0077] In some embodiments of the present application, the first sintering is performed in an inert atmosphere.

[0078] In some embodiments of the present application, the inert atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.

[0079] In some embodiments of the present application, the temperature of the first sintering is 200-500°C, for example, 200°C, 260°C, 300°C, 320°C, 370°C, 400°C, 430°C, 480°C, 500°C, etc., and the time of the first sintering is 2-6h, for example, 2h, 4h, 6h, etc.

[0080] In some embodiments of the present application, the heating rate of the first sintering is 5-15°C / min, for example, 5°C / min, 8°C / min, 12°C / min, 13°C / min, 15°C / min, etc.

[0081] In some embodiments of the present application, the particle size D50 of the lithium supplement intermediate is 8-13um, such as 8um, 9um, 12um, 13um, etc.

[0082] In some embodiments of the present application, in step (2), the graphene, the cellulose and the organic solvent are first mixed, and the first mixed product is filtered and dried to obtain a cellulose composite powder; and then the cellulose composite powder, the lithium supplement intermediate and the organic solvent are second mixed.

[0083] Premixing graphene and cellulose separately can make the two tightly bonded. Under the interaction of graphene's non-polar surface and cellulose's hydrophobic molecular chain, premixing can promote graphene exfoliation and cellulose nano-crystallization, promote the formation of a highly dense structure between the two materials, make it have an ultra-high specific surface area, form a continuous conductive network, and provide a path for rapid ion diffusion and rapid charge transmission.

[0084] In some embodiments of the present application, the speed of the first mixing is 1000-1600 r / min, for example, 1000 r / min, 1200 r / min, 1300 r / min, 1400 r / min, 1600 r / min, etc., and the time of the first mixing is 2-5 h, for example, 2 h, 3 h, 5 h, etc.

[0085] In some embodiments of the present application, the solid-liquid ratio of the graphene and the cellulose to the organic solvent is (0.1-0.2) mg:1 ml.

[0086] In some embodiments of the present application, the particle size D50 of the cellulose composite powder is ≤30um, for example, 30um, 26um, 23um, 20um, 18um, 15um, etc.

[0087] In some embodiments of the present application, the organic solvent includes ethanol and / or N-methylpyrrolidone.

[0088] In some embodiments of the present application, in the second mixing step, the solid-liquid ratio of the lithium supplement intermediate and the cellulose composite powder to the organic solvent is (1-10) mg: 1 ml.

[0089] In some embodiments of the present application, the speed of the second mixing is 1000-1600r / min, for example, 1000r / min, 1200r / min, 1300r / min, 1400r / min, 1600r / min, etc., preferably 1100-1400r / min, and the time of the second mixing is 0.5-2h, for example, 0.5h, 0.8h, 1.2h, 1.5h, 2h, etc.

[0090] High-speed shearing further achieves the exfoliation of graphene, nano-sizing of cellulose and in-situ composite hybridization of the two, and makes them evenly dispersed on the surface of the lithium supplement.

[0091] In some embodiments of the present application, in step (3), the second sintering is performed under an inert atmosphere. Preferably, the inert atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.

[0092] In some embodiments of the present application, in step (3), the temperature of the second sintering is 200-400°C, for example, 200°C, 260°C, 280°C, 320°C, 360°C, 400°C, etc., and the time of the second sintering is 1-3h, for example, 1h, 2h, 3h, etc.

[0093] In some embodiments of the present application, in step (3), the heating rate of the second sintering is 2-10°C / min, for example, 2°C / min, 5°C / min, 8°C / min, 10°C / min, etc.

[0094] An embodiment of the present application further provides a lithium-ion battery, wherein the positive electrode of the lithium-ion battery comprises the composite lithium supplement agent described in the first aspect of the present application or the composite lithium supplement agent obtained by the preparation method described in the second aspect of the present application.

[0095] In the process of using composite lithium supplementers to prepare lithium-ion batteries, the slurry dispersion effect is good during the homogenization process, and the viscosity and solid content meet the coating requirements, which can improve the process window, produce low electrode resistance, and the prepared lithium-ion battery has low internal resistance, small polarization, and long cycle life.

[0096] In some embodiments of the present application, the mass percentage of the composite lithium supplement in the positive electrode material of the lithium-ion battery is 0.1%-10%, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.7%, 3.6%, 4.3%, 5.7%, 6.8%, 7.4%, 8.2%, 9.1%, 10%, etc.

[0097] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0098] Example 1

[0099] A method for preparing a composite lithium supplement comprises the following steps:

[0100] (1) LiOH and NiO were mixed evenly in a molar ratio of 4:1 and ball-milled at a speed of 800 r / min for 3 h. The ball-milled product was then sintered at a high temperature in a vacuum environment at a heating rate of 8°C / min. When the sintering temperature reached 900°C and maintained for 4 h, a lithium supplement powder with a particle size D50 of 12.1 μm was obtained.

[0101] (2) Mix lithium supplement powder and V6O 13 The powders were mixed evenly in a mass ratio of 100:3 and sintered at low temperature in a nitrogen inert atmosphere. The sintering heating rate was 8°C. When the sintering temperature reached 400°C and kept for 4 hours, a coated V6O with a particle size D50 of 12.1 μm was obtained. 13 An intermediate for lithium supplements.

[0102] (3) Graphene and ethyl cellulose were mixed in a mass ratio of 1:0.9, and then the mixture of graphene and ethyl cellulose and ethanol solution were evenly mixed in a shear mixer at a solid-liquid ratio of 0.14 mg / ml. The mixing shear speed was 1400 r / min and the shear time was 3 h. After the shearing was completed, the mixture was centrifuged and filtered to obtain a cellulose composite powder with a particle size D50 of 22 um.

[0103] (4) The lithium supplement intermediate and the cellulose composite powder were mixed in a mass ratio of 100:3, and then the mixture of the lithium supplement intermediate and the cellulose composite powder was sheared and mixed with an ethanol solution at a solid-liquid ratio of 6 mg / ml. The mixing shear speed was 1400 r / min, the shear time was 1 h, and the mixture was centrifuged and filtered for drying. It was sintered at a low temperature in a nitrogen inert atmosphere. The sintering heating rate was 5°C / min. When the sintering temperature reached 300°C and maintained for 2 h, a composite lithium supplement with a particle size D50 of 12.3 um was obtained.

[0104] Example 2

[0105] The difference between the composite lithium supplement agent described in Example 2 and that in Example 1 is that during the preparation of the composite lithium supplement agent described in Example 2, the mass ratio of the lithium supplement agent to the vanadium source layer is different from that in Example 1.

[0106] The specific steps include:

[0107] A method for preparing a composite lithium supplement comprises the following steps:

[0108] (1) LiOH and NiO were mixed evenly in a molar ratio of 4:1 and ball-milled at a speed of 800 r / min for 3 h. The ball-milled product was then sintered at a high temperature in a vacuum environment at a heating rate of 8°C / min. When the sintering temperature reached 900°C and maintained for 4 h, a lithium supplement powder with a particle size D50 of 12.1 μm was obtained.

[0109] (2) Mix lithium supplement powder and V6O 13 The powders were mixed evenly in a mass ratio of 100:5 and sintered at low temperature in a nitrogen inert atmosphere. The sintering heating rate was 8°C. When the sintering temperature reached 400°C and kept for 4 hours, a coated V6O with a particle size D50 of 12.1 μm was obtained. 13 An intermediate for lithium supplements.

[0110] (3) Graphene and ethyl cellulose were mixed in a mass ratio of 1:0.9, and then the mixture of graphene and ethyl cellulose and ethanol solution were evenly mixed in a shear mixer at a solid-liquid ratio of 0.14 mg / ml. The mixing shear speed was 1400 r / min and the shear time was 3 h. After the shearing was completed, the mixture was centrifuged and filtered to obtain a cellulose composite powder with a particle size D50 of 22 um.

[0111] (4) The lithium supplement intermediate and the cellulose composite powder were mixed in a mass ratio of 100:3, and then the mixture of the lithium supplement intermediate and the cellulose composite powder was sheared and mixed with an ethanol solution at a solid-liquid ratio of 6 mg / ml. The mixing shear speed was 1400 r / min, the shear time was 1 h, and the mixture was centrifuged and filtered for drying. It was sintered at a low temperature in a nitrogen inert atmosphere. The sintering heating rate was 5°C / min. When the sintering temperature reached 300°C and maintained for 2 h, a composite lithium supplement with a particle size D50 of 12.3 um was obtained.

[0112] Example 3

[0113] The difference between the composite lithium supplement agent described in Example 3 and Example 1 is that during the preparation of the composite lithium supplement agent described in Example 3, the mass ratio of the lithium supplement agent to the vanadium source layer is 100:7.

[0114] Example 4

[0115] The difference between the composite lithium supplement described in Example 4 and Example 1 is that methyl cellulose is used instead of ethyl cellulose in the preparation process of the composite lithium supplement described in Example 4.

[0116] Example 5

[0117] The difference between the composite lithium supplement described in Example 5 and Example 1 is that carboxymethyl cellulose is used instead of ethyl cellulose in the preparation process of the composite lithium supplement described in Example 5.

[0118] Example 6

[0119] The difference between the composite lithium supplement described in Example 6 and Example 1 is that hydroxyethyl cellulose is used instead of ethyl cellulose in the preparation process of the composite lithium supplement described in Example 6.

[0120] Example 7

[0121] The difference between the composite lithium supplement described in Example 7 and Example 1 is that hydroxypropyl cellulose is used instead of ethyl cellulose in the preparation process of the composite lithium supplement described in Example 7.

[0122] Example 8

[0123] The only difference between the composite lithium supplement described in Example 8 and Example 1 is that hydroxypropyl methylcellulose is used instead of ethyl cellulose in the preparation process of the composite lithium supplement described in Example 8.

[0124] Example 9

[0125] The composite lithium supplement described in Example 9 is different from that in Example 1 only in that the mass ratio of graphene to cellulose in the preparation process of the composite lithium supplement described in Example 9 is 1:0.6.

[0126] Example 10

[0127] The composite lithium supplement described in Example 10 is different from that in Example 1 only in that the mass ratio of graphene to cellulose in the preparation process of the composite lithium supplement described in Example 10 is 1:1.2.

[0128] Embodiment 11

[0129] The composite lithium supplement described in Example 11 is different from that in Example 1 only in that the mass ratio of graphene to cellulose in the preparation process of the composite lithium supplement described in Example 11 is 1:1.5.

[0130] Example 12

[0131] The difference between the composite lithium supplement described in Example 12 and Example 1 is that the rotation speed of the mixing and shearing of the lithium supplement intermediate and the cellulose composite powder during the preparation of the composite lithium supplement described in Example 12 is 800 r / min.

[0132] Example 13

[0133] The only difference between the composite lithium supplement described in Example 13 and Example 1 is that during the preparation of the composite lithium supplement described in Example 13, the speed of mixing and shearing the lithium supplement intermediate and the cellulose composite powder is 1100 r / min.

[0134] Embodiment 14

[0135] The only difference between the composite lithium supplement described in Example 14 and Example 1 is that during the preparation of the composite lithium supplement described in Example 14, the speed of mixing and shearing the lithium supplement intermediate and the cellulose composite powder is 1700 r / min.

[0136] Comparative Example 1

[0137] The difference between the composite lithium supplement agent described in Comparative Example 1 and Example 1 is that TiO2 is used instead of the vanadium source during the preparation of the composite lithium supplement agent described in Comparative Example 1.

[0138] Comparative Example 2

[0139] The difference between the composite lithium supplement agent described in Comparative Example 2 and Example 1 is that Cr2O3 is used instead of the vanadium source during the preparation of the composite lithium supplement agent described in Comparative Example 2.

[0140] Comparative Example 3

[0141] The difference between the composite lithium supplement agent described in Comparative Example 3 and Example 1 is that during the preparation of the composite lithium supplement agent described in Comparative Example 3, only the vanadium source layer is coated.

[0142] The specific steps include:

[0143] A method for preparing a composite lithium supplement comprises the following steps:

[0144] (1) LiOH and NiO were mixed evenly in a molar ratio of 4:1 and ball-milled at a speed of 800 r / min for 3 h. The ball-milled product was then sintered at a high temperature in a vacuum environment at a heating rate of 8°C / min. When the sintering temperature reached 900°C and maintained for 4 h, a lithium supplement powder with a particle size D50 of 12.1 μm was obtained.

[0145] (2) Mix lithium supplement powder and V6O 13 The powders were mixed evenly in a mass ratio of 100:3 and sintered at low temperature in a nitrogen inert atmosphere. The sintering heating rate was 8°C. When the sintering temperature reached 400°C and kept for 4 hours, a coated V6O with a particle size D50 of 12.1 μm was obtained. 13 Composite lithium supplement.

[0146] Comparative Example 4

[0147] The difference between the composite lithium supplement agent described in Comparative Example 4 and Example 1 is that during the preparation of the composite lithium supplement agent described in Comparative Example 4, only a mixture of graphene and cellulose is used to coat the lithium supplement agent.

[0148] The specific steps include:

[0149] A method for preparing a composite lithium supplement comprises the following steps:

[0150] (1) LiOH and NiO were mixed evenly in a molar ratio of 4:1 and ball-milled at a speed of 800 r / min for 3 h. The ball-milled product was then sintered at a high temperature in a vacuum environment at a heating rate of 8°C / min. When the sintering temperature reached 900°C and maintained for 4 h, a lithium supplement powder with a particle size D50 of 12.1 μm was obtained.

[0151] (2) Graphene and ethyl cellulose were mixed in a mass ratio of 1:0.9, and then the mixture of graphene and ethyl cellulose and ethanol solution were evenly mixed in a shear mixer at a solid-liquid ratio of 0.14 mg / ml. The mixing shear speed was 1400 r / min and the shear time was 3 h. After the shearing was completed, the mixture was centrifuged and filtered to obtain a cellulose composite powder with a particle size D50 of 22 um.

[0152] (3) The lithium supplement powder and the cellulose composite powder were mixed in a mass ratio of 100:3, and then the mixture of the lithium supplement powder and the cellulose composite powder was sheared and mixed with an ethanol solution at a solid-liquid ratio of 6 mg / ml. The mixing shear speed was 1400 r / min, the shear time was 1 h, and the mixture was centrifuged and filtered for drying. The mixture was sintered at a low temperature in a nitrogen inert atmosphere at a sintering heating rate of 5°C / min. When the sintering temperature reached 300°C, it was kept warm for 2 h to obtain a composite lithium supplement.

[0153] Comparative Example 5

[0154] The difference between the composite lithium supplement agent described in Comparative Example 5 and Example 1 is that in the preparation process of the composite lithium supplement agent described in Comparative Example 5, the lithium supplement agent is first coated with a mixture of graphene and cellulose, and then coated with a vanadium source.

[0155] The specific steps include:

[0156] A method for preparing a composite lithium supplement comprises the following steps:

[0157] (1) LiOH and NiO were mixed evenly in a molar ratio of 4:1 and ball-milled at a speed of 800 r / min for 3 h. The ball-milled product was then sintered at a high temperature in a vacuum environment at a heating rate of 8°C / min. When the sintering temperature reached 900°C and maintained for 4 h, a lithium supplement powder with a particle size D50 of 12.1 μm was obtained.

[0158] (2) Graphene and ethyl cellulose were mixed in a mass ratio of 1:0.9, and then the mixture of graphene and ethyl cellulose and ethanol solution were evenly mixed in a shear mixer at a solid-liquid ratio of 0.14 mg / ml. The mixing shear speed was 1400 r / min and the shear time was 3 h. After the shearing was completed, the mixture was centrifuged and filtered to obtain a cellulose composite powder with a particle size D50 of 22 um.

[0159] (3) The lithium supplement powder and the cellulose composite powder were mixed in a mass ratio of 100:3, and then the mixture was sheared and mixed with an ethanol solution at a solid-liquid ratio of 6 mg / ml. The mixing shear speed was 1400 r / min and the shear time was 1 h. The mixture was centrifugally filtered and dried. The mixture was sintered at a low temperature in a nitrogen inert atmosphere. The sintering heating rate was 5°C / min. When the sintering temperature reached 300°C, it was kept warm for 2 h to obtain a lithium supplement intermediate.

[0160] (4) Releasing the lithium supplement intermediate with V6O 13 The powders were mixed evenly in a mass ratio of 100:3, and sintered at low temperature in a nitrogen inert atmosphere at a sintering heating rate of 8°C. When the sintering temperature reached 400°C, it was kept warm for 4 hours to obtain a composite lithium supplement.

[0161] Study on the performance of the composite lithium supplement described in Examples 1-14 and Comparative Examples 1-5 of the present application

[0162] The composite lithium supplement described in Examples 1-14 of the present application and Comparative Examples 1-5, accounting for 2.5% of the total mass of the positive electrode sheet, was added to the positive electrode active material, mixed evenly using a conventional process, and prepared by coating, rolling and die-cutting to obtain a positive electrode sheet, and assembled together with the negative electrode sheet and the separator by a stacking or winding process to obtain a soft-pack battery, and the process processing performance data and electrochemical performance data were obtained.

[0163] The positive electrode slurry formula is prepared according to the mass ratio of lithium iron phosphate: lithium replenisher (the composite lithium replenisher described in Examples 1-14 and Comparative Examples 1-5): conductive carbon black: polyvinylidene fluoride (PVDF) of 93.8:3.2:1:2, and the negative electrode slurry formula is prepared according to the mass ratio of graphite: conductive carbon black: carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 95.8:1.2:1.2:1.8, and the electrolyte is a mixture of 1 mol / L LiPF6 and ethyl cellulose (EC): epoxy molding compound (EMC): dimethyl carbonate (DMC) (volume ratio of 4:3:3).

[0164] The battery's first week charge and discharge current rate is 0.05C / 0.1C, the first week voltage range is 2.5-4.2V, the cycle current rate is 0.2C / 0.2C, the voltage range is 2.5-3.65V, the battery design capacity is 3.6Ah, the surface free lithium content after the lithium supplement agent is left for 24 hours, the positive electrode slurry process data and the battery's first week charge gram capacity, and the capacity retention rate for 800 cycles are tested. The data are shown in Table 1 below.

[0165] Table 1

[0166]

[0167] It can be seen from Table 1 that based on different mass ratios of different lithium supplements and vanadium sources, the vanadium source ratios used in Examples 1 and 2 are better, the free lithium content on the surface of the lithium supplement is low, the homogenization processing test data is qualified, and the lithium battery has good electrical performance. The vanadium source ratio in Example 3 is higher, the coating layer is slightly thick, which is not conducive to ion transmission, the polarization internal resistance is relatively large, and the cycle is slightly better. The preferred mass ratio of the lithium supplement and the vanadium source is 100:(3-5).

[0168] Based on the mixing of graphene with different celluloses, the cellulose types selected in Examples 4, 5, and 6 are not suitable, the mixing effect of preparing cellulose composite powder is poor, which is not conducive to uniform coating of lithium supplement, the processing effect is general, and the battery electrical performance is poor, while the lithium supplement and lithium battery prepared by the cellulose types selected in Examples 1, 7, and 8 have better performance. Cellulose is preferably ethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose.

[0169] Based on the different mass ratios of graphene and cellulose, the mixed quality of graphene and cellulose used in Example 1 and Example 9 is relatively good, and the performance of the lithium supplement and the lithium battery is better. The mixed mass ratio in Example 9 is too small and the mixed mass ratio in Example 11 is too large, which is not conducive to improving the performance of the lithium supplement and the performance of the prepared lithium battery. Therefore, the mass ratio of graphene and cellulose is preferably 1: (0.8-1.3).

[0170] Based on the different second mixing shear speeds, the mixing speeds adopted in Example 1 and Example 13 are better, the cellulose composite is evenly coated on the surface of the lithium supplement agent, and the performance of the lithium supplement agent and the lithium battery is better. The mixing speed in Example 12 is too low and the mixing speed in Example 14 is too high, both of which are not conducive to improving the performance of the lithium supplement agent. Therefore, the second mixing speed is preferably 1000-1600r / min.

[0171] Comparing the coating with different metal compounds, comparative examples 1 and 2 respectively use metal element compounds of the same period for coating, which has poor improvement effect on the lithium supplement agent and is not conducive to the performance of the prepared lithium battery.

[0172] Comparative Example 3 only coated the vanadium source, Comparative Example 4 only coated the cellulose composite powder, and Comparative Example 5 first coated the cellulose composite powder and then coated the vanadium source, all of which had poor improvements on the processing performance and electrochemical performance of the lithium supplement agent, which is not conducive to the electrical performance of the prepared lithium battery.

[0173] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A composite lithium supplement, characterized in that: These include lithium supplements; A vanadium source layer coated on the surface of the lithium supplementing agent; A graphene and cellulose composite layer coated on the surface of the vanadium source layer.

2. The composite lithium supplement according to claim 1, characterized in that: The lithium supplement comprises a lithium source and a metal compound; Preferably, the lithium source comprises one or more of LiOH, Li2CO3, Li2O, Li2O2, LiNO3 and Li2SO4; Preferably, the metal compound includes one or more of Fe2O3, Fe3O4, FeCl3, Fe(OH)3, NiO, NiSO4 and Ni(OH)2; Preferably, the molar ratio of the lithium source to the metal compound is (2-7):1; Preferably, the particle size D50 of the lithium supplement is 8-13 um.

3. The composite lithium supplement according to claim 1, characterized in that: The vanadium source layer includes vanadyl oxalate, ammonium metavanadate, vanadium pentoxide, V6O 13 , VO2(B) and V2O3; And / or, the mass ratio of the lithium supplement agent to the vanadium source layer is 100:(1-8), preferably 100:(3-5).

4. The composite lithium supplement according to claim 1, characterized in that: The cellulose includes one or more of hydroxypropyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose and ethyl cellulose; preferably, the cellulose includes one or more of hydroxypropyl cellulose, hydroxypropyl methyl cellulose and ethyl cellulose; And / or, the mass ratio of the graphene to the cellulose is 1:(0.6-1.6), preferably 1:(0.8-1.3); And / or, the mass ratio of the total mass of the lithium supplement and the vanadium source layer to the mass of the composite layer is 100:(1-8); And / or, the particle size D50 of the composite lithium supplement agent is 8-13 um.

5. The method for preparing the composite lithium supplement according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing a lithium supplement agent and a vanadium source and performing a first sintering to obtain a lithium supplement agent intermediate coated with a vanadium source layer; (2) mixing the lithium supplement intermediate, graphene, cellulose and an organic solvent to obtain a mixed solution; (3) filtering the mixed solution, drying the solid matter obtained by filtration and performing a second sintering to obtain the composite lithium supplement agent.

6. The method for preparing the composite lithium supplement according to claim 5, characterized in that: In step (1), the preparation method of the lithium supplement agent comprises the following steps: mixing a lithium source and a metal compound and ball milling them, and sintering the ball milling product in a vacuum environment to obtain the lithium supplement agent; Preferably, the ball milling speed is 600-1200 r / min, and the ball milling time is 2-5 h; Preferably, the temperature of the sintered ball-milled product is 700-1000° C., and the time of the sintered ball-milled product is 2-6 hours; Preferably, the heating rate of the sintered ball-milled product is 5-15° C. / min.

7. The method for preparing the composite lithium supplement according to claim 5, characterized in that: The first sintering is performed in an inert atmosphere, preferably, the inert atmosphere includes a nitrogen atmosphere and / or an argon atmosphere; And / or, the temperature of the first sintering is 200-500° C., and the time of the first sintering is 2-6 hours; And / or, the heating rate of the first sintering is 5-15°C / min; And / or, the particle size D50 of the lithium supplement intermediate is 8-13 um.

8. The method for preparing the composite lithium supplement according to claim 5, characterized in that: In step (2), the graphene, the cellulose and the organic solvent are first mixed, and the first mixed product is filtered and dried to obtain a cellulose composite powder; and the cellulose composite powder, the lithium supplement intermediate and the organic solvent are second mixed; Preferably, the speed of the first mixing is 1000-1600 r / min, and the time of the first mixing is 2-5 h; Preferably, in the first mixing step, the solid-liquid ratio of the graphene and the cellulose to the organic solvent is (0.1-0.2) mg: 1 ml; Preferably, the organic solvent comprises ethanol and / or N-methylpyrrolidone; Preferably, the particle size D50 of the cellulose composite powder is ≤30 um.

9. The method for preparing the composite lithium supplement according to claim 8, characterized in that: In the second mixing step, the solid-liquid ratio of the lithium supplement intermediate and the cellulose composite powder to the organic solvent is (1-10) mg: 1 ml; And / or, the speed of the second mixing is 1000-1600 r / min, and the time of the second mixing is 0.5-2 h; And / or, in step (3), the second sintering is performed under an inert atmosphere, preferably, the inert atmosphere includes a nitrogen atmosphere and / or an argon atmosphere; And / or, in step (3), the temperature of the second sintering is 200-400° C., and the time of the second sintering is 1-3 hours; And / or, in step (3), the heating rate of the second sintering is 2-10°C / min.

10. A lithium ion battery, characterized in that: The positive electrode of the lithium-ion battery comprises the composite lithium supplement agent according to any one of claims 1 to 4 or the composite lithium supplement agent obtained by the preparation method according to any one of claims 5 to 9; Preferably, the mass percentage of the composite lithium supplement in the positive electrode material of the lithium ion battery is 0.1%-10%.

Citation Information

Patent Citations

  • Positive electrode lithium supplement additive and preparation method and application thereof

    CN115215376A

  • Positive electrode lithium supplementing material and preparation method and application thereof

    CN115312887A

  • Lithium supplement agent and preparation method thereof, positive pole piece and secondary battery

    CN116505103A

  • Positive electrode lithium supplement agent, positive electrode material, battery and electric equipment

    CN118017036A

  • Lithium iron phosphate positive electrode material and preparation method and application thereof

    CN118479440A